Idiopathic Hypoparathyroidism and Severe Hypocalcemia in Pregnancy - Carine Ghassan Richa; Ali Ihsan Issa; Akram Salim Echtay; Mohamad Souheil El Rawas (Case Reports in Endocrinology)
The objective of this study is to report a case of severe hypocalcemia secondary to hypoparathyroidism in a pregnant woman. We report a case of a 45-year-old woman who presented for tonico-clonic seizure in the third trimester of gestation. She was diagnosed with idiopathic hypoparathyroidism for the first time during pregnancy. She was successfully treated with calcium and calcitriol in the rest of her pregnancy with resolution of symptoms but her infant was born with hypercalcemia and secondary hyperparathyroidism due to the late maternal presentation. To the best of our knowledge, hypoparathyroidism is a disorder rarely observed during pregnancy, resulting in most cases from surgical thyroidectomy.